Variation at ABO histo-blood group and FUT loci and diffuse and intestinal gastric cancer risk in a European population. - Duell, E; Bonet, C; Muñoz, X; Lujan-Barroso, L; Weiderpass, E; Boutron-Ruault, M; Racine, A; Severi, G; Canzian, F; Rizzato, C; Boeing, H; Overvad, K; et al. (Wiley-Liss Inc., 2015)
ABO blood serotype A is known to be associated with risk of gastric cancer (GC), but little is known how ABO alleles and the fucosyltransferase (FUT) enzymes and genes which are involved in Lewis antigen formation [and in Helicobacter pylori (H. pylori) binding and pathogenicity] may be related to GC risk in a European population. The authors conducted an investigation of 32 variants at ABO and FUT1-7 loci and GC risk in a case-control study of 365 cases and 1,284 controls nested within the EPIC cohort (the EPIC-Eurgast study). Four variants (including rs505922) in ABO, and allelic blood group A (AO+AA, odds ratio=1.84, 95%CI=1.20-2.80) were associated with diffuse-type GC; however, conditional models with other ABO variants indicated that the associations were largely due to allelic blood group A. One variant in FUT5 was also associated with diffuse-type GC, and four variants (and haplotypes) in FUT2 (Se), FUT3 (Le) and FUT6 with intestinal-type GC. Further, one variant in ABO, two in FUT3 and two in FUT6 were associated with H. pylori infection status in controls, and two of these (in FUT3 and FUT6) were weakly associated with intestinal-type GC risk. None of the individual variants surpassed a Bonferroni corrected p-value cutoff of 0.0016; however, after a gene-based permutation test, two loci [FUT3(Le)/FUT5/FUT6 and FUT2(Se)] were significantly associated with diffuse- and intestinal-type GC, respectively. Replication and functional studies are therefore recommended to clarify the role of ABO and FUT alleles in H. pylori infection and subtype-specific gastric carcinogenesis.